2007
DOI: 10.1002/bmc.818
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HPLC and CE methods for the determination of cetirizine dihydrochloride in human plasma samples

Abstract: Two methods, capillary electrophoresis (CE) and high-performance liquid chromatography (HPLC), for analysis of cetirizine dihydrochloride in small sample volumes of human plasma were compared. The CE and HPLC assays were developed and validated by analyzing a series of plasma samples containing cetirizine dihydrochloride in different concentrations using these two methods. The extraction procedure is simple and no complicated purification steps or derivatization are required. The analysis time in the HPLC meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…The LLOQ for urine spiked standard solutions were found to be 1ng/ml for CTZ and 3.5 ng/ml for AMB. The LLOQ was found lower than that obtained by the previous methods [5,[10][11][12]19,21]. Chromatograms recorded for CTZ and AMB at LLOQ concentration are given in Figs.…”
Section: Specificity and Sensitivitycontrasting
confidence: 70%
See 1 more Smart Citation
“…The LLOQ for urine spiked standard solutions were found to be 1ng/ml for CTZ and 3.5 ng/ml for AMB. The LLOQ was found lower than that obtained by the previous methods [5,[10][11][12]19,21]. Chromatograms recorded for CTZ and AMB at LLOQ concentration are given in Figs.…”
Section: Specificity and Sensitivitycontrasting
confidence: 70%
“…Due to this effect, estimation of drugs in lower nano grams turns into a failed maneuver and resorts in to LC-MS technique, which is a cost escalating practice. Column switching (boxcar chromatography) is a powerful technique for the separation and cleanup of complex multi component samples with higher accuracy [2].There is a published research article on narrow bore column switching HPLC method for the estimation of CTZ in plasma [3], in vitro estimation of CTZ using HPLC and spectrophotometry [4], estimation of CTZ in human plasma [5][6][7][8][9] and urine by HPLC [10,11], a comparative study between HPLC and CE methods for the determination of cetirizine in human plasma [12], estimation of cetirizine in animal plasma [13,14] and methods to estimate CTZ in plasma by LC/MS technique [15,16]. Similarly, methods have been reported for the estimation of AMB in plasma and urine by HPLC and LC/MS methods [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sombra et al (2005), while investigating synthetic adulterants in plant protection, also concluded that the CE method was faster, and that the HPLC method had lower detection limits. Conversely, Kowalski and Plenis (2007), in a quantification study on cetirizine di-hydrochloride in human plasma, obtained faster analysis using the HPLC, equivalent detection limits between the two methods, and lower solvent consumption with the CE method. In those studies, the costs, composition and volume of residues generated, and the required treatment and its cost were not measured and compared directly.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…A number of analytical methods have been used to quantify cetirizine in pharmaceutical formulations and biological fluids (serum, plasma, urine, and tears) including high performance thin layer chromatography (HPTLC) [6], gas chromatography [7], HPLC with ultraviolet detection [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPLC with fluorescence detection (pre-column derivatization) [25], HPLC with on-line liquid scintillation counting [26], and capillary electrophoresis (CE) [14,[27][28][29]. However, these methods have a number of disadvantages; for example, they require a large volume of sample (≥1.0 mL), and have long run time, low separation resolution, and poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%